Berpikir Kreatif Dalam Pengembangan Plug-And-Play Sistem Dan Database Case Study Sensor Suhu DHT11 - Farid Baskoro; Bambang Suprianto; Lilik Anifah; Ekohariadi .; aristyawan Nurdiansyah (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2023)
Creative thinking is an important thing that must be possessed by every individual because it plays an important role in the progress of a country. One aspect of creative thinking is innovation which can combine existing knowledge with experience to create the development of new ideas. The purpose of this study is to implement creative thinking from the aspect of innovation in developing a DHT11 temperature and humidity sensor plug-and-play system with a database and communicative thinking in establishing good communication between devices and humans. The method used in this study was an experiment conducted by taking a sample of 120 data. The results of this study indicate a plug-and-play process developed by a scanning process to find connected PORTs without having to do configuration, showing a comparison of the DHT11 error value with a comparator that reaches 0.628% in temperature values and 0.428% in humidity values. This study also shows 10080 monitoring data for one week's temperature and humidity values obtained from the interface that has been made and the results of the data acquisition will be directly stored in the database which will later be used for further research.